Exploring genotype–phenotype relationships of the CRABP2 gene on growth traits in beef cattle. Issue 1 (2nd January 2020) - Wen, Yi-Fan; Zheng, Li; Niu, Hui; Zhang, Guo-Liang; Zhang, Gui-Min; Ma, Yi-Lei; Tian, Yi-Ran; Liu, Yan-Rong; Yang, Peng; Yang, Di-Yi; Lei, Chu-Zhao; Dang, Rui-Hua; et al.
Abstract: Cellular retinoic acid binding protein 2 ( CRABP2 ) is essential to myoblast differentiation. However, there was no report about the function of CRABP2 gene in cattle. This study explored the association of CRABP2 gene polymorphisms with growth traits in cattle breeds by several methods, such as DNA sequencing, PCR, PCR–RFLP and forced PCR–RFLP. Two sequence variants were determined. There were 621 individuals in six cattle breeds from China for the experiment, and three breeds were used to test validation of polymorphisms and extent of linkage disequilibrium (LD). The results showed that both SNPs (SNP1, g.2458 G > T, SNP2, g.3878 G > A) were in intron1. Two SNPs were in low linkage disequilibrium. Association analysis suggested that SNP1 had the significant difference on growth traits with body height, height at hip cross and body slanting length ( P < .05), while SNP2 showed a significant difference in growth traits with body height, height at hip cross and body slanting length (P < .05). The results of this investigation displayed that the CRABP2 gene is an available candidate gene and may be used for breed selection and conservation.